Sofrimento e prazer no trabalho : um estudo sobre os processos de saúde-doença de professores da educação municipal - Reis, Geny Gonçalves dos (2017)
The present research aims to understand and analyze the suffering in the work from the perspective of the teacher of Basic Education. As suffering and pleasure are not incompatible, but a contradictory and inseparable pair, we deal not only with what makes suffering at work, but how teachers deal with this suffering, just as we consider the possibilities of pleasure that arise in this struggle. In this investigation we examine the reality of a municipal public school in the peripheral zone of a municipality in the State of São Paulo. The research is based on the theoretical reference of the Psychodynamics of Work, as well as on studies concerning the Brazilian basic education that analyze the developments of the State Reform in educational policies and in the teaching work. The analysis is anchored in data obtained in the years 2015 and 2016 through a questionnaire answered by a sample of 29 teachers; semi-structured interviews conducted with 8 teachers; official documents of Brazilian fundamental education and municipal education; data from the Division of Medicine and Safety at Work concerning the deviations for health motives of the municipal teachers. The categories of analysis constructed - conditions and work routine; recognition and work relations; autonomy and meaning in the work; the feminine condition in the teaching work - allowed to understand the conflicts between suffering and pleasure and in what way they interfere in the work, subjectivity and health. The daily work is composed of high loads of hours/class, intensification of the rhythms and demands and invasion of labor in the spaces of non work, in a context of objective and subjective precarization. In the working relationships established between the peers working in the same school year the recognition is configured as punctual, if not limited. Strategies have been identified to fight for recognition. About half of the group stays in school every year and part of it shares a political ideal of transformative education. The collective, contradictory unity contains internal quarrels and disagreements, which hinder and/or create obstacles to cooperative and solidarity relations. There are objective and subjective impediments that alienate them from the authentic meaning of work. Suffering and illness were identified in the narrative of six of the eight interviewees. Pleasure and suffering coexist, but suffering overcomes pleasure, in a context of precariousness and degradation of oneself and of the collectives, subjecting workers to wear and tear, so as to affect their well-being, health, professional identity and quality of work.